Implementasi Kurikulum 2013 Dalam Pembelajaran Akuntansi(Studi Kasus Di Smk Negeri Se-Surakarta) - Ertanti, Pipit; , Dra. Titik Asmawati, S.E., M.Si (2017)
This research aims to know: 1) Implementation of curriculum implementation 2013 in accounting learning, 2) success learners learn by using kurikulu 2013, 3) obstacles faced by accounting teacher in implementation of curriculum 2013. The research method used in this research is research method qualitative. Research location in SMK Negeri 1 and SMK Negeri 6 Surakarta. Data collection techniques in this study are interviews, observation and documentation. The validity of data is done through triangulation. Data analysis is done by data reduction, data presentation and conclusion. The results of this study are 1) Implementation of the 2013 curriculum in overall accounting subjects performed well when viewed from: a. The competence of educators such as accounting teachers at SMK Negeri 1 and SMK Negeri 6 Surakarta is in accordance with the curriculum and field of science, b. Accounting lessons at SMK Negeri 1 and SMK Negeri 6 Surakarta are owned by all students, c. The lesson plan of accounting lesson (RPP) prepared by accounting teachers at SMK Negeri 1 and SMK Negeri 6 Surakarta is in accordance with the components and systematics of the curriculum RPP 2013 d. Implementation of learning that occurred in SMK Negeri 1 and SMK Negeri 6 Surakarta in accounting subjects are in accordance with the curriculum of 2013 such as learning using a scientific approach, learning takes place effectively that has made learners become active and learning methods used by accounting teachers vary, and E. Accounting teachers at SMK Negeri 1 and SMK Negeri 6 Surakarta in accounting subjects conduct assessment in accordance with the implementation of the 2013 curriculum that is carrying out authentic assessment, 2) the success of learners learn by using the curriculum 2013 in accounting subjects at SMK Negeri 1 and SMK Negeri 6 Surakarta Achieve a pretty good learning mastery and make learners active, and 3) Accounting teachers at SMK Negeri 1 and SMK Negeri 6 Surakarta have difficulty in providing bookbased accounting curriculum 2013 for grip students because there is no accounting package package based curriculum 2013 issued By the government.